2016
DOI: 10.1002/jwmg.21101
|View full text |Cite
|
Sign up to set email alerts
|

Winter diet and hunting success of Canada lynx in Colorado

Abstract: Information regarding the diet of Canada lynx (Lynx canadensis) at the southernmost extent of its range is critical for managing the species under current and predicted climate conditions. Therefore, from 1999-2009, we investigated winter diet and hunting strategies of Canada lynx in Colorado, USA by tracking individuals in the snow to identify sites where lynx encountered and killed prey. Similar to other parts of lynx range, snowshoe hares (Lepus americanus) were the primary winter food in Colorado, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…This pattern was expected and consistent with Canada lynx specializing on snowshoe hares (Elton and Nicholson , Krebs et al. , Ivan and Shenk ). Finally, male lynx demonstrated a positive functional response (increasing use with increasing availability) for advanced regeneration while females demonstrated additive use (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This pattern was expected and consistent with Canada lynx specializing on snowshoe hares (Elton and Nicholson , Krebs et al. , Ivan and Shenk ). Finally, male lynx demonstrated a positive functional response (increasing use with increasing availability) for advanced regeneration while females demonstrated additive use (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…), but the mature structure class is where hares are most accessible for lynx (Fuller et al. , Ivan and Shenk ). This mechanism received demographic support by Kosterman (), who demonstrated that female lynx with core areas of highly connected mature forest and intermediate levels of regenerating forests had the highest probability of producing a litter.…”
Section: Discussionmentioning
confidence: 99%
“…That is, adding recreational activities to our models may have, in some sense, been a proxy for adding stem density and horizontal cover, which is a primary factor affecting lynx resource use across the species’ southern periphery (Squires et al. , McCann and Moen , Ivan and Shenk , Holbrook et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…, Thornton et al. , Ivan and Shenk ) that is less likely to exclude backcountry skiers compared with motorized recreationists traveling at high speeds (Olson et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…, Holbrook et al. ) and lynx are more successful at killing snowshoe hares in mature forest than regenerating forest (Ivan and Shenk ). In addition, lynx exhibit strong selection for mature forest and use this structural stage twice as much as any other during both winter and summer seasons (Holbrook et al.…”
Section: Methodsmentioning
confidence: 99%